Tvorba produktů pro destinaci Jižní Slovácko - Kozová, Martina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá problematikou tvorby produktů ve vybrané turistické destinaci Jižní Slovácko. V úvodní části jsou popsány teoretická východiska práce, především podstata managementu a marketingu destinace, destinačních produktů a jejich tvorby. Ve druhé části jsou realizovány analýzy zaměřené na zhodnocení současného stavu destinace, včetně rozboru turistické poptávky a porovnání s největšími konkurenty. Závěrečná část se zabývá návrhem produktů, které mají zvýšit atraktivitu turistické destinace pro návštěvníky.

This thesis is dealing with problems of creating products in the tourist destination South Slovácko. In the introductory part there are described theoretical solutions of thesis, first of all essence of the management and marketing of destination, touristic products and product creation. In the second part there are realized analysis, which are focused on evaluate of current destination condition, including analysis of touristic demand and comparison with the biggest competitors. Closing part is dealing with the design of the products, which should make touristic destinations more attractive.
Products Creation for Destination of South Slovácko
Keywords: cestovní ruch; turistická destinace; marketing; produkt cestovního ruchu; marketingový mix; destinační management; tourism; tourist destination; marketing; tourism product; marketing mix; destination management